Spatial Spillovers and the Effects of Fiscal Stimulus: Evidence from Pandemic-Era Federal Aid for State and Local Governments - Jeffrey Clemens; John Kearns; Beatrice Lee; Stan Veuger (American Enterprise Institute (AEI), 2023)
We analyze the extent to which US federal aid to state and local governments during the COVID-19 pandemic had effects that spilled over across state lines. We find that federal assistance had a positive overall effect on state and local government employment that stems largely from the direct effect of states' own aid allocation. To be more precise, we find that each 878,000 in federal assistance created or preserved one state or local job, a third of which was driven by cross-state spillovers. Our analysis of the effects of federal aid on aggregate economic activity generally finds null effects through either direct or spillover channels.
Keywords: 330